Aspek Sosial Ekonomi Masyarakat Lokal dalam Pengelolaan Desa Wisata Pantai Trisik, Kulonprogo - Arina Pramusita; Eska Nia Sarinastiti (Jurnal Pariwisata Terapan, 2018)
Trisik beach is one of potential tourism attraction in Banaran Village Kulonprogo, it has a lot of potential to be developed. Trisik beach offers several attractive tourism attractions such as beach, mangrove plants, turtle conservation, and agrotourism. Among its potential, agrotourism had a big chance to developed. Most of the community in Trisik beach village are actively involved and get the benefit from agriculture. The development of community based tourism requires the participation of local communities in the entire development phases starting from planning, implementation, and supervision. However, public participation is often completely overlooked. This study aims to analyzed development of tourism and formulate the model of community involvement in tourism development. The study is conducted  in Trisik beach area, Banaran, Galur, Kulonprogo. The proces of collecting data through the study literature, in depth interview, and field observation. The analytical method used is descriptive analysis.